Conditions of Contracts and Dinner Invitations: traces of the Architect in Dunedin Builders’ Association Archives - McCarthy, Christine (Architectural History Aotearoa, 2007)
The institutional records of builders in Otago in the 1890s are more comprehensively preserved that those of architects. These are primarily represented by the archives of the Dunedin Builders and Contractors’ Association, and they provide a specific point of view of the profession of architect during the decade. This paper will examine how these records represent the relationships between builders and architects and the emerging attempts to define these trades and professions with their distinct contributions to, and benefits gained from, the processes of design and building architecture.